Parametric Evaluation for Extraction of Catechin from Areca Catechu Linn Seeds using Supercritical CO2 Extraction (Jurnal Teknologi (Sciences & Engineering), 2015)
Supercritical fluid extraction is an advanced extraction technique which has been proven its efficiency and selectivity in numerous studies. Dense gas with diffusivity nearing liquid and viscosity closed to gas phase, supercritical fluid can provide better performance in the extraction of natural and heat sensitive active compounds. Areca Catechu Linn or commonly known as betel nut can be easily found in tropical country especially in south-east and south of Asia with India as its world largest producer. Phenolic compound present in Areca Catechu Linn are condensed tannins and also catechin. Catechin is a highly active compound with several properties such as anti-depressant, anti-oxidant, anti-viral, anti-flammatory and anti-aging which are in demand by cosmetic and pharmaceutical industries. The aim of this study is to determine the best particle size, solvent flow rate, presence of modifier or co-solvent, and time of extraction for this pre-treatment study. Average particle size of 0.1774 mm (dp4) was detected as the best particle size for the extraction process with 3 mL/min solvent flow rate with 5% methanol added to solvent. Modifier presence enhances the extraction by improving the ability to extract more polar compound such as catechin. The best catechin recovery was observed at 3mL/min, solvent composition of 95:5 (SC-CO2:MeOH) at the temperature of 70áµ’C and pressure of 30 MPa with 47.38 Î¼g catechin/g extracts.